The Faith, Activity, and Nutrition (FAN) Dissemination and Implementation Study: 24-Month Organizational Maintenance in a Countywide Initiative - Sara Wilcox; Sara Wilcox; Ruth P. Saunders; Ruth P. Saunders; Danielle Jake-Schoffman; Brent Hutto (Frontiers Media S.A., 2020)
Introduction: Despite the important role that faith-based organizations can play in eliminating health disparities, few studies have focused on organizational change and maintenance of interventions in this setting, making their long-term impact unknown. This study reports 24-month maintenance of the Faith, Activity, and Nutrition (FAN) program in a southeastern county. Previously reported findings of reach, adoption, implementation, and effectiveness are also summarized.Methods: Church coordinators from 35 intervention churches (97% predominantly African American) located in a rural, medically underserved county in South Carolina were interviewed at baseline (2015), and 12- and 24-months post-training regarding implementation of physical activity (PA) and healthy eating (HE) components of the FAN program. Guided by the RE-AIM framework, organizational maintenance was defined as church coordinator-reported 24-month implementation of the four FAN components (providing opportunities, setting guidelines/policies, sharing messages, engaging pastor). Repeated measures analyses (mixed models) examined change in implementation over time. Churches were also classified as maintainers, non-sustained implementers, and low implementers for each FAN component. Statistical analyses were conducted in 2019.Results: Church coordinators reported significantly greater implementation of both PA and HE FAN components at 12 and 24 months compared to baseline (medium to large effects). The percentage of churches classified as maintainers ranged from 21 to 42 and 27 to 94% across PA and HE components, respectively. Most churches (58% for PA, 97% for HE) were maintaining at least one FAN component at 24 months.Conclusions: These promising findings position FAN well for the national implementation study now underway.Trial Registration: This study is registered at www.clinicaltrials.gov NCT02868866.